Solusi Numerik pada Persamaan Korteweg-De Vries Equation menggunakan Metode Beda Hingga - Haizar, Maulana Rifky; Rizki, Miptahul; Robbaniyyah, Nuzla Af'idatur; Syechah, Bulqis Nebulla; Salwa, Salwa; Awalushaumi, Lailia (Eigen Mathematics Journal, 2024)
The Korteweg-de Vries (KdV) equation is a nonlinear partial differential equation that has a key role in wave physics and many other disciplines. In this article, we develop numerical solutions of the KdV equation using the finite difference method with the Crank-Nicolson scheme. We explain the basic theory behind the KdV equation and the finite difference method, and outline the implementation of the Crank-Nicolson scheme in this context. We also give an overview of the space and time discretization and initial conditions used in the simulation. The results of these simulations are presented through graphical visualizations, which allow us to understand how the KdV solution evolves over time. Through analysis of the results, we explore the behavior of the solutions and perform comparisons with exact solutions in certain cases. Our conclusion summarizes our findings and discusses the advantages and limitations of the method used. We also provide suggestions for future research in this area.